Bank Solvency Stress Tests with Fire Sales - Thomas Breuer; Martin Summer; Branko Urošević (Oesterreichische Nationalbank (OeNB), 2021)
We present a simple and operational yet rigorous framework that combines current methods of bank solvency stress tests with a description of fire sales. We demonstrate the applicability of our framework to the EBA stress testing exercise. Fire sales are described by an equilibrium model which balances leverage improvements and drops in security prices. The differences in bank losses caused by fire sales are significant and go beyond the trivial fact that with deleveraging we will get bigger losses. It is shown that ignoring potential deleveraging effects can show institutions as resilient which are in fact fragile and thus create a false sense of resilience.
Keywords: C18; C44; C60; G01; G32; M48; 330; Stress Testing; Fire Sales; Deleveraging; Systemic Risk